RANCANG BANGUN MESIN PENUMBUK SAGU UBI KAYU UNTUK PROSES PEMBUATAN BERAS ARUK DENGAN MOTOR LISTRIK 0,5 HP - Mahdi .; Firlya Rosa; Saparin .; Eka Sari Wijianti (Jurnal Turbulen, 2018)
The pulverization of cassava sago is one of the main of traditional aruk rice.To get a chewy and very chewy level of sago requiresto pulverize ± 50 minutesfor 1 kg cassava sago. To speed up the pulverization process, it was designed a sagopulverization machine with a 0.5 HP electric motor power. The design method uses the French method, with the pulley and v-belt as atransmission system to actuate the eccentric shaft so that the pounder will move up and down. The fixed variable is time and it will set for 10 minutes and 12 minutes with result analysis using visualization method to 10 respondents. The force that generated by eccentric shaft and transmitted to the pounder of 1.010 N produce the chewy level of sago at 10 minutes to pulverization process  with capacity 6 kg / hour and the very chewy level at time 12 minutes with capacity 5 kg / hour.This machine will  reduce time of pulverization process until 76-80% compared to the manual process. Keywords: Aruk rice, grinding machines, electric motors, elasticity